SPECTRAL ANALYSIS OF REFERENCE SIGNAL AND OF HF SIGNAL REFLECTED FROM THE IONOSPHERE BEATS - Pushin, V. F.; Chernogor, L. F. (Видавничий дім «Академперіодика», 2014)
Topicality of this work is due to the necessity of studying the physical effects associated with the processes in the magnetosphere and the ionosphere. The HF Doppler radar of vertical sounding is used for observations. The spectral analysis of the beat mode for detecting the Doppler filtering of acoustic waves is used for data processing. Spectral analysis is also used to select oscillations in the frequency range of 1−12 Hz (ULF electromagnetic waves). Processing technique was verified by the numerical experiment. ULF waves are experimentally established to be observed in the daytime with a frequency of 1.5 Hz.Key words: simulation of HF signal beatings, Doppler radar, ionosphere, spectral analysis, electromagnetic ULF waves, acoustic wavesManuscript submitted: 14.01.2014Radio phys. radio astron. 2014, 19(2): 160-169REFERENCES1. AFRAIMOVICH, E. L., 1982. Interference methods of radio sounding of the ionosphere. Moscow: Nauka Publ. (in Russian). 2. GERSHMAN, B. N., 1974. Dynamics of ionospheric plasma. Moscow: Nauka Publ. (in Russian). 3. DAVIES, K., 1990. Ionospheric radio. London: Peter Peregrinus Ltd. 590 p. DOI: https://doi.org/10.1049/PBEW031E 4. SCHUNK, R. W. and NAGY, A. F., 2000. Ionospheres: Physics, Plasma Physics, and Chemistry, Atmospheric and Space Science Series. Cambridge: Cambridge University Press, 554 p. DOI: https://doi.org/10.1017/CBO9780511551772 5. GINZBURG, V. L., 1967. The propagation of electromagnetic waves in a plasma. Moscow: Science Publ. (in Russian). 6. NISHIDA, A., 1980. Geomagnetic diagnosis of the magnetosphere. Moscow: Mir Publ. (in Russian). 7. ALPEROVICH, L. S. and FEDOROV, E. N., 2007. Hydromagnetic Waves in Magnetosphere and Ionosphere, Series: Astrophysics and Space Science Library, Springer Netherlands, vol. 353, 418 p. DOI: https://doi.org/10.1007/978-1-4020-6637-5 8. GORELIK, G. S., 2008. Oscillations and waves. Moskow: Fizmatlit Publ.(in Russian). 9. GRIGORYEV, G. I., 1999. Acoustic-gravitational waves in the Earth's atmosphere (review). Izv. Universities. Radiophysics. vol. 1, no. 42, pp. 3–25 (in Russian). 10. OTNES, R. and ENOXON, L., 1982. Applied analysis of time series. Moscow: Mir Publ. 428 p. (in Russian). 11. GERSHMAN, B. N., YERUKHIMOV, L. M., AND YASHIN, Yu. Ya., 1984. Wave phenomena in the ionosphere and cosmic plasma. Moscow: Nauka Publ.(in Russian). 12. ARTRU, J., FARGES, T., AND LONGNONNÉ, P. H., 2004. Acoustic waves generated from seismic surface waves: propagation properties determined from Doppler sounding observations and normal-mode modeling. Geophys. J. Int. vol. 158, pp. 1067–1077. DOI: https://doi.org/10.1111/j.1365-246X.2004.02377.x 13. LIU, J. Y., TSAI, Y. B., CHEN, S. W., LEE, C. P., CHEN, Y. C., YEN, H. Y., and CHANG, W. Y., 2006. Giant ionospheric disturbances excited by the M9.3 Sumatra earthquake of 26 December 2004. Geophys. Res. Lett. vol. 33, Is. 2, id. L02103.